2014
DOI: 10.1037/css0000004
|View full text |Cite
|
Sign up to set email alerts
|

Creative histories: Memories of past lives and measures of creativity.

Abstract: Experiencing memories of past lives is anomalous in Western culture. Such experiences may signify an overinclusive cognitive style, associated with creative ability. Accordingly, are reports of past life memory (PLM) associated with creativity? Is PLM associated with measures of overinclusiveness? To investigate these issues, we conducted two studies. In study one, we recruited subjects who reported having recovered memories of previous lives, and compared them to demographically matched comparison subjects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…After all, several previous studies have indicated relationship between reduced latent inhibition and creativity (e.g., Carson et al, 2003;Kéri, 2011;Meyersburg et al, 2014;Peterson et al, 2002). One reason for the differential results may be differences between blocking and latent inhibition tasks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After all, several previous studies have indicated relationship between reduced latent inhibition and creativity (e.g., Carson et al, 2003;Kéri, 2011;Meyersburg et al, 2014;Peterson et al, 2002). One reason for the differential results may be differences between blocking and latent inhibition tasks.…”
Section: Discussionmentioning
confidence: 98%
“…It has been found that individuals scoring high on creativity measures will exhibit greater learning about irrelevant stimuli than individuals scoring low in creativity. This has been evidenced by performance on latent inhibition tasks, involving learning about irrelevant stimuli (e.g., Carson, Peterson, & Higgins, 2003;Kéri, 2011;Meyersburg, Carson, Mathis, & McNally, 2014;Peterson, Smith, & Carson, 2002). In a latent inhibition task, participants experience a repeated presentation of a stimulus (e.g., an image of a food) by itself.…”
mentioning
confidence: 99%
“…After all, several previous studies have indicated relationship between reduced latent inhibition and creativity (e.g., Carson et al, 2003;Kéri, 2011;Meyersburg et al, 2014;Peterson et al, 2002). One reason for the differential results may be differences between blocking and latent inhibition tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that individuals scoring high on creativity measures will exhibit greater learning about irrelevant stimuli than individuals scoring low in creativity. This has been evidenced by performance on latent inhibition tasks, involving learning about irrelevant stimuli (e.g., Carson, Peterson, & Higgins, 2003;Kéri, 2011;Meyersburg, Carson, Mathis, & McNally, 2014;Peterson, Smith, & Carson, 2002). In a latent inhibition task, participants experience a repeated presentation of a stimulus (e.g., an image of a food) by itself.…”
Section: Resultsmentioning
confidence: 99%
“…However, if memories of past lives are accompanied by a strong sensation of traveling back in time, it could be argued that people, or at least some individuals, can mentally revisit time coordinates preceding their own birth. Nevertheless, these cases would remain exceptional instances of MTT, as memories of past lives are exceptional occurrences not only within Western culture but also in cultures where the belief in reincarnation is prevalent ( Meyersburg et al, 2014 ). Furthermore, even in these exceptional cases, the limits imposed by their personal history would still restrict the potential destinations they can reach.…”
Section: Traveling To a Temporal Destination Different From The Presentmentioning
confidence: 99%